Effectiveness of Platelet-rich Plasma Therapy and Limberg Flap Reconstruction in the Management of Pilonidal Sinus Disease: A Prospective Observational Study - S Vinith Balaji; K Thinagaran; Reegan Jose; Najeem Fazil; Mohana Vamsi; Arafath Iqbal (Journal of Clinical and Diagnostic Research)
Introduction: Pilonidal Sinus Disease (PSD) is a chronic inflammatory condition affecting the sacrococcygeal region, commonly seen in young adults. The ideal treatment remains debated, with surgical techniques such as Limberg flap reconstruction and non surgical approaches like Platelet-Rich Plasma (PRP) therapy being explored for their efficacy in reducing recurrence and improving wound healing. Aim: To compare the wound healing duration, postoperative pain levels, recurrence rates and postoperative complications between PRP therapy and Limberg flap reconstruction in the management of PSD. Materials and Methods: A prospective observational study was conducted in the Department of General Surgery at SRM Medical College Hospital and Research Institute, Chennai, Tamil Nadu, India from January to December 2024, involving 62 patients. Adults aged 18 to 65 years with Type I or II PSD, who were fit for surgery and willing to provide informed consent, were included. Patients were randomly allocated into two groups: Group A (PRP Therapy, n=31) and Group B (Limberg Flap Reconstruction, n=31). In Group A, PRP was applied both intraoperatively and during the postoperative follow-up, while Group B underwent excision followed by flap reconstruction using the Limberg flap technique. Data on key outcomes, including wound healing time, pain levels {measured using the Visual Analog Scale (VAS)}, recurrence rates and postoperative complications, were collected over a 6-month period. Statistical analysis was conducted using Statistical Package for the Social Sciences (SPSS) version 29.0, with a p-value <0.05 considered statistically significant. Results: The mean wound healing duration was significantly shorter in Group A (29.0±7.0 days) compared to Group B (39.0±8.0 days, p-value <0.001). Pain scores (VAS) were similar on Day 2 (p-value=0.358), but Group A experienced significantly less pain from Day 3 onwards (p-value<0.05). Recurrence rates were significantly lower in Group A {4 (12.9%)} compared to Group B {10 (32.3%), p-value=0.029}. Postoperative complications were less frequent in Group A {24 (77.4%) had no complications vs. 19 (61.3%) in Group B, p=0.045}, with Group B showing higher rates of seroma formation {5 (16.1%) vs. 3 (9.7%)} and wound dehiscence {4 (12.9%) vs. 1 (3.2%)}. Infection rates were similar in both groups, at 3 (9.7%). Conclusion: PRP therapy presents a promising and effective alternative for managing PSD, potentially enhancing recovery and minimising complications.